Ablation treatment for Barrett oesophagus: what depth of tissue destruction is needed?. Issue 7 (1st July 1999) - Ackroyd, R; Brown, N J; Stephenson, T J; Stoddard, C J; Reed, M W
Abstract : AIM: To establish the depth of Barrett's columnar epithelium and normal squamous oesophageal epithelium, in order to determine the depth of destruction required in ablation treatment for Barrett oesophagus. METHODS: Histological specimens from 100 cases of Barrett oesophagus and 100 samples of normal squamous oesophageal epithelium were studied. Using a system of multiple measurements until the change in cumulative mean values varied by less than 5%, the overall mean and normal range of depth was calculated for each type of epithelium. RESULTS: Barrett columnar epithelium is minimally thicker (mean (SEM) 0.50 (0.004) mm; range 0.39 to 0.59 mm) than normal squamous epithelium (0.49 (0.003) mm; 0.42 to 0.58 mm), although this difference is probably too small to be of clinical relevance. CONCLUSIONS: Although there are numerous clinical reports of various methods of ablation treatment for Barrett oesophagus, little attention has been paid to the depth of tissue destruction required. This is the first study to look specifically at this issue, and it provides information on the necessary depth of epithelial ablation.